Isotopic Analysis of Sporocarp Protein and Structural Material Improves Resolution of Fungal Carbon Sources - Chen, Janet; Hofmockel, Kirsten S.; Hobbie, Erik A. (Frontiers in Microbiology, 2016)
Fungal acquisition of resources is difficult to assess in the field. To determine whether fungi received carbon from recent plant photosynthate, litter or soil-derived organic (C:N bonded) nitrogen, we examined differences in δ13C among bulk tissue, structural carbon, and protein extracts of sporocarps of three fungal types: saprotrophic fungi, fungi with hydrophobic ectomycorrhizae or fungi with hydrophilic ectomycorrhizae. Sporocarps were collected from experimental plots of the Duke Free-air CO2 enrichment (FACE) experiment during and after CO2 enrichment. The differential 13C labeling of ecosystem pools in CO2 enrichment experiments was tracked into fungi and provided novel insights into organic nitrogen use. Specifically, sporocarp δ13C as well as δ15N of protein and structural material indicated that fungi with hydrophobic ectomycorrhizae used soil-derived organic nitrogen sources for protein carbon, fungi with hydrophilic ectomycorrhizae used recent plant photosynthates for protein carbon and both fungal groups used photosynthates for structural carbon. Saprotrophic fungi depended on litter produced during fumigation for both protein and structural material.